Grammatical Equivalence of English-Indonesian Translation of Compound-Complex Sentences in Iadc Workover Completion Manual - Oktaviani, Santi; Sutopo, Djoko (Universitas Negeri Semarang, 2018)
During the translation of IADC Workover Completion Manual, especially the compound-complex sentences, grammatical equivalence is crucial in order to produce accurate, acceptable, and readable translations. Therefore, this study is conducted to evaluate the realization of grammatical equivalence in English–Indonesian translation of compound-complex sentences in the manual and its relation to the translation quality. This study is a descriptive qualitative study. The researcher used document to collect the data of the compound-complex sentences. Besides, questionnaire and interview were completed by the target readers and the expert readers to assess the translation quality. The findings presents that out of 106 English compound-complex sentences that are translated to Indonesian, 74 (69.8%) of them are grammatically equivalent and 32 (30.1%) of them are not grammatically equivalent. It means that the 74 sentence translations’ structures are equivalent. In addition, the translations are literal and there are no shifts. In contrast, 32 non-grammatical equivalent translations are due to their free translations and lead to the translation shifts. From the findings, it can also be concluded that the grammatical equivalence influences the accuracy, the acceptability, and the readability of the translations for the target readers. On the other hand, for the expert readers, the grammatical equivalence only affects readability.